Preferred Coping Actions for Anxiety among Psychiatric Outpatient Waiting Room Visitors - Desikaliana Desikaliana; Mustanir Mustanir; Marthoenis Marthoenis; Marty Mawarpury (GLOBAL HEALTH SCIENCE GROUP, 2025)
Anxiety and psychological disturbance are commonly managed through coping actions that reflect individual beliefs, social norms, and perceived accessibility of care. Understanding preferred actions in routine service environments such as psychiatric outpatient waiting rooms is important to support culturally sensitive mental health education and referral strategies. This study aimed to describe the most preferred action when experiencing anxiety or psychological disturbance among individuals present in a psychiatric outpatient waiting room. A descriptive cross-sectional survey was conducted in the waiting room of an outpatient psychiatric polyclinic at a mental hospital. Respondents consisted of patients, accompanying family members, and nurses who were present during the data collection period. A total of 100 respondents were recruited using a convenience sampling technique. Data were collected using a self-administered questionnaire that recorded age category, education level, and one most preferred coping action when experiencing anxiety or psychological disturbance. Data were analysed using descriptive statistics. Religious worship and spiritual practices were the most frequently preferred action, selected by 50% of respondents. Ruqyah was chosen by 20%, professional help seeking through psychologists or psychiatrists by 15%, self-management meditation by 9%, and visiting a traditional healer by 6%. Adults represented the largest age category (55%), and senior high school was the most common education level (43%). Preferences for coping with anxiety in this setting were dominated by religious and spiritual practices, while professional help seeking was less frequently prioritised.